Relationship between Knowledge and Attitude with the Dangers of Bullying in High School Students - Sadya Bustomi; Mukhlasin; Prihayati; Diah Nurul Qulbi; Rizka Fitriani; Jessica Edrea Valeska (Health and Technology Journal (HTechJ), 2025)
Bullying is a common issue in school environments and can have severe negative impacts on students' mental, social, and academic well-being. This study examined the Relationship between Knowledge and Attitude with the Dangers of Bullying in High School Students. A quantitative cross-sectional approach was used, involving 60 eleventh-grade students selected through total sampling. Data were collected using questionnaires distributed before and after the health education intervention and analyzed using univariate and bivariate tests. The univariate results showed that most respondents had high levels of bullying behavior (71.7%), low knowledge (68.3%), and negative attitudes (51.7%). After the intervention, improvements were observed in both knowledge and attitudes. Bivariate analysis revealed a significant relationship between knowledge and bullying (p = 0.017) and between attitude and bullying (p = 0.033). Health education proved effective as a promotive and preventive strategy for fostering positive behavior and empathy among adolescents. Therefore, schools should integrate health education into student development programs to create a safe and violence-free learning environment. This study contributes to bullying prevention through a structured, evidence-based educational approach.